2018
DOI: 10.1016/j.jadohealth.2018.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Research Gaps in Sexual and Gender Minority Adolescents' Substance Use and Misuse

Abstract: Sexual and gender minority (SGM) adolescents report higher rates of substance use and misuse compared with their heterosexual and cisgender peers [1,2]. These disparities span across several substances, including alcohol, tobacco, marijuana, and prescription and illicit drugs, as well as more recent popular substances such as electronic cigarettes [3]. Disparities in substance use are well documented among sexual minority adolescents, and a growing body of research has more recently documented disparities amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…Characteristics of the sample are summarized in Table 1. The mean6SD age of participants was 2863 (range [21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Most participants were non-Hispanic white (78%); 49% of participants identified as cisgender female, 39% as cisgender male, and 12% as gender minorities (i.e., transgender, gender nonbinary, or gender queer).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristics of the sample are summarized in Table 1. The mean6SD age of participants was 2863 (range [21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Most participants were non-Hispanic white (78%); 49% of participants identified as cisgender female, 39% as cisgender male, and 12% as gender minorities (i.e., transgender, gender nonbinary, or gender queer).…”
Section: Resultsmentioning
confidence: 99%
“…Few studies have qualitatively examined relationships between experiences of LGBTQ-related stressors, substance use, and sociocultural influences in adolescence and young adulthood. This research is needed to understand youth substance use initiation and escalation, how these processes contribute to the development of substance use disorders, and effective substance use disorder prevention strategies (24,30,31). This study qualitatively examined narratives from LGBTQ-identified young adults about their substance use initiation, escalation, and use in adolescence and young adulthood vis-à-vis their LGBTQ identities.…”
Section: Highlightsmentioning
confidence: 99%
“…53 Research on smoking and vaping in transgender and non-binary adolescents (and rainbow youth more broadly) is an area for future research, as overseas research suggests these populations have a higher prevalence of smoking and vaping than cisgender and heterosexual adolescents. 54…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Taken together, cannabis use (Whiteford et al, 2013) and minority status stressors (Saewyc, 2011) can place substantial burden on adolescents' quality of life. To date, there is a paucity of research examining relationships among adolescents who identify as nonbinary gender or as LGBTQ and substance use (Mereish, 2018).…”
Section: Gender and Sexuality And Cannabis Usementioning
confidence: 99%